The Comprehension of COVID-19 Mitigation in the Nonformal Education - Musa, Safuri; Muhyiddin, Yusuf; Siswanto, Siswanto; Nurhayati, Sri (Society, 2022)
The world condition is currently being affected by the COVID-19 pandemic, including the behavior of human life and the teaching and learning process. Educators and educational personnel are overwhelmed in learning activities by changing appropriate learning strategies. Thus, it is necessary to understand COVID-19 mitigation literacy. This study aims to analyze the correlation between the COVID-19 mitigation literacy comprehension on educators and educational personnel’s life behavior. Also, to examine the learning strategies used during the pandemic in nonformal education units in West Java. The IBM SPSS Statistics 24.0 program analyzed this correlation study descriptively and inferentially. The results showed a high correlation between the understanding of COVID-19 pandemic mitigation literacy and the life behavior of educators and educators at nonformal education units in West Java Province. They used a blended learning strategy, with WhatsApp as the dominant application. The obstacles in implementing the learning strategy were poor connections in some areas and the lack of operational costs in purchasing internet quota packages.